SCHOOL LIBRARY DEVELOPMENT VS POLICY PROVISION: DIVERGENCE OR CONVERGENCE? - Mojapelo, Samuel; Dube, Luyanda (Mousaion: South African Journal of Information Studies, 2016)
A policy and legal framework for school libraries is a guiding framework for the provision, development and management of school libraries. Similarly, it is a lever that standardises school library development, management and practice. Although the existence of a policy does not guarantee the development of efficient and functional school libraries, its inherent value cannot be overemphasised. It is widely documented that in South Africa, only 7.2 per cent of public schools have functional school libraries, which are crucial to enrich the quality of teaching and learning and support learners and teachers. The aim of this study was, firstly, to analyse the legal and policy provision for school libraries in South Africa; and secondly, to examine the state of school libraries in Limpopo province, South Africa. The study further sought to establish whether there is divergence or convergence between policy provision and the status of school libraries in Limpopo. The study adopted a quantitative research paradigm and triangulated utilising questionnaires and document analysis as instruments to collect data. The study established that there is a regime of policies related to school libraries, most of which are still in draft form. Furthermore, the study confirmed that provision of policy does not necessarily translate into an efficient school library system. The distinct divergence means that there is no correlation between policy provision and practice. The study recommends that the existing school library policies should be streamlined, adopted and implemented to scale up the development of efficient and functional school libraries in Limpopo.